The knowledge needed for advisors in the Strict Sensu Graduate Studies in Education: a review study (Práxis Educativa, 2024)
Stricto Sensu Graduate Programs brings together the highest degrees of academic training in Brazil. At the core of the process the mentees and advisors are found. The relationship between these two agents is similar to that of the mentor and his/her disciple, in which the mentor teaches the disciple what he/she knows. This review article aims to investigate the knowledge needed by advisors in Stricto Sensu Graduate Programs in the 21st century, based on articles published between 2000 and 2022 on the Education Resources Information Center (ERIC) platform. The results point to the need for more investigations into guidance, especially from the point of view of the advisors. Among the knowledge necessary for these, it is highlighted those related to research and publication methods, the development of a schedule to assist in conducting the research, the acquisition and management of resources and the professional training of the mentees. Notably, the relationships between these agents are linked to the student’s successful completion of the process.Keywords: Graduate education. Stricto Sensu. Advisors. Knowledge.